MODELING OF QUALITY MANAGEMENT SYSTEM FOR ELECTRONIC LEARNING RESOURCES: THE INTEGRATED AND DIFFERENTIATED APPROACHES - Kravtsov, Г.М. (Journal of Information Technologies in Education (ITE), 2012)
Results on modeling of quality management system of electronic information resources on the basis of the analysis of its elements functioning with use of the integrated and differentiated approaches are presented. Application of such model is illustrated on an example of calculation and optimization of parameters of a quality management system at the organization of the co-ordinated work of services of monitoring, an estimation of quality and support of electronic learning resources.